A TRANSMIDIAÇÃO NA FORMAÇÃO DO LEITOR CONTEMPORÂNEO - Santos da Silva Júnior, João (Revista Gênero e Interdisciplinaridade, 2021)
The present article aims to outline the different paths necessary for the formation of the contemporary reader, the objective is to bring the light of knowledge that the transmedia today, translates as a fortuitous perspective in the formation of the reader, given the different possibilities that permeate and concatenate with the formative act. This article is structured from a description of what is transmedia and how it happens contributing to/in the formation of the contemporary reader. The bibliographic study of the book "Culture of Convergence" by Henry Jenkins (2009) is very much based on the structure of this work and also the translated reading of works such as: the Harry Potter saga and The Slave Isaura. In addition to understanding how the transmediatic process contributes to the formation of the reader, we aim to identify the step by step, which converge in the (re) structuring of knowledge and readers.